Suomen peltojen maalajit, muokkauskerroksen syvyys ja maan happamuus - Halonen, Reino; Juusela, Taneli (Agricultural and Food Science, 1957)
The soil types of the fields in Finland, the depth of the tilled layer and the acidity (pH) of the tilled layer as well as of the subsoil are presented on the basis of an investigation performed in 1954 in the whole country, employing the regional division shown in Fig. 1. In the investigation the random sampling method was used in such a manner that the above-mentioned questions were studied in one field compartment per each thousand hectares of cultivated land, the field compartments being determined by lot. The depth of the tilled layer was measured at a point at a distance of about one quarter of the length of the field compartment from its lower end. The soil samples for the determination of soil type and pH were also taken from the same spot. The soil type was determined on the basis of a sample taken from the subsoil; it was entered as mineral soil if the mud or peat layer had a thickness of not more than 30 cm. If clay soil contained humus in excess of 2 %, it was entered as muddy clay. Of the mineral soil types, clays are the most common soil types of the cultivated fields in southwestern and southern Finland. Parallel with the diminishing percentage of clay soil types towards the north, that of coarse graded soils and of organic soil types increases. Till soils are more common in the central parts of the country. The normal depth of the tilled layer in the whole country is 17.5 cm. In southern and southwestern Finland it is greater than in the other parts of the country. As a rule, the tilling is shallowest on till soils and deepest on clay soils. The acidity of the soil is less in southern and southwestern Finland than in the other parts of the country, judging by the samples from the tilled layer and by those from the subsoil. The organic soil types show a higher acidity than the mineral soils. In the mineral soils the acidity of tilled layer and subsoil is nearly the same, whereas in organic soils the acidity increases with increasing depth Acidity and relative content of finely divided soil fractions seem to be correlated in mineral soils. For instance, the normal acidity of the subsoil is 5.6 in coarse sand, 5.7 in fine sand, 5.8 in loam, 5.9 in silt and 6.0—6.1 in clay.